A Multi‐Array Back‐Projection Approach for Tsunami Warning. Issue 14 (9th July 2020) - Xie, Y.; Meng, L.
Abstract: Recent development of dense strong‐motion networks and seismic array processing enables rapid tsunami predictions based on the back‐projection (BP) approach. We develop a multi‐array local BP method (MLBP) using seismic networks with epicentral distance from 0.7° to 3.5°. The local BPs using individual arrays are first calculated and are then merged into a single image of the rupture process. This multi‐array approach circumvents the issue of artifact in single‐array BP caused by the overlapping of multiple phases and coda waves. Based on the local BP approach, tsunami predictions are available 7 min after the origin time. Case studies of the 2003 Mw 8.1 Tokachi‐oki and the 2011 Mw 9.0 Tohoku earthquakes show that their rupture zones are well resolved and are comparable with principal slip areas inferred from tsunami observations. The amplitude and arrival time errors of the predicted tsunami waves are within −1.59 to 3.74 m and −10.0 to 10.0 min, which are sufficiently small for warning purposes. Plain Language Summary: Accurate prediction of tsunami waves for residents who are close to the tsunami source requires fast characterization of tsunami‐genic earthquakes. In this research, we develop a tsunami warning approach based on earthquake source observations using multiple dense clusters of seismic stations installed near the coastal region. At a given stage during an earthquake, the recorded seismic wavefield is back‐propagated to retrieve the direction of the seismic source with respect to each cluster of stations. By combining direction information determined at each station group, we retrieve the principle slip fault area that is most responsible for tsunami generation. A simplified earthquake source model is then constructed to predict the tsunami arrival time and height. By adopting local seismic stations within 80–400 km away from the earthquake sources, we show that the tsunami warning can be issued 7 min after the earthquake origin time. Our case studies of the 2003 Mw 8.1 Tokachi‐oki and the 2011 Mw 9.0 Tohoku earthquakes show that our approach adequately reproduces the tsunami observations. The height errors of the predicted tsunami waves are within −1.59 to 3.74 m; the errors of the arrival times are within −10.0 to 10.0 min, which are sufficiently small for warning purposes. Key Points: We develop a tsunami warning approach based on a multi‐array back‐projection (BP) method using local seismic networks (0.7°<Δ <3.5°) The multi‐array BP circumvents the issue of artifacts in single‐array BP caused by the overlapping of multiple phases and coda waves Case studies of the 2003 M8.1 Tokachi and the 2011 M9.0 Tohoku earthquakes demonstrate fast and accurate predictions for tsunami warning